UiTM Sarawak won three criteria in the campus category of Vice Chancellor's Quality Award or Anugerah Kualiti Naib Canselor (AKNC) - Ch'ng, Looi Chin (UiTM Sarawak, 2016)
The winners of the Vice Chancellor's Quality Award or Naib Anugerah Kualiti Naib Canselor (AKNC) 2015 were announced in the annually held Bulan Inovasi ceremony on 23rd December 2015 at Dewan Agung Tuanku Canselor, UiTM Selangor. UiTM Sarawak has won the grand championship for a record of four times in the inaugural 2000, 2003, 2004 and 2005. During the ceremony, UiTM Sarawak was adjudged the winner in three out of eight criteria in the campus category behind UiTM Terengganu which won four criteria and the campus category champion title while UiTM Johor managed to win one criteria. The three campuses were shortlisted as finalists for the campus category. Academy of Contemporary Islamic Studies won the Faculty category while the Tun Abdul Razak Library or PTAR was the winner for the Department/Unit/Center category